Office Communication Competencies for Vocational High School in Industri 4.0 - Widianingrum, Riska; Aw, Suranto; Hermanto, Febrika Yogie; Sholikah, Mar’atus (Dinamika Pendidikan, 2020)
This study aims to explore the information about industry needs for office communication competence in the 4.0 industrial revolution era. Competency suitability is one of the things supporting objective achievement of vocational education implementation. The development of office communication competencies also needs to be scrutinized and adjusted so that students can learn both at school and industry. This research is a case study research conducted using a descriptive method with qualitative approach and analyzed using the Miles Hubberman model which includes stages of data reduction, data presentation, data verification, and data inference. The results of this study indicate that office communication competencies explicitly contained in the 2013 revised edition of the 2017 curriculum are still relevant to be taught in schools and are still needed in the industry. Several competencies need to be updated and added to support students' skills in dealing with the development of work in the industry related to office communications in the 4.0 industrial revolution era to improve the office work effectiveness, such as (1) information management using social media, web, and online application of goods or services sales; (2) mastery of communication using social media, the web, and online application of goods or services sales; and (3) mastery of international languages.